2016
DOI: 10.1371/journal.pone.0164192
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of In Vivo Absorption of Lactate and Modulation of Short Chain Fatty Acid Absorption from the Reticulorumen of Non-Lactating Cattle Fed High Concentrate Diets

Abstract: Short-chain fatty acids (SCFAs) and lactate are endproducts of rumen fermentation and important energy sources for the host ruminant. Because their rapid accumulation results in ruminal acidosis, enhancement of the absorption of SCFA and lactate across reticuloruminal wall is instrumental in increasing energy supply and preventing ruminal acidosis in cattle. This study investigated whether the reticuloruminal absorption of SCFAs and lactate was altered by different strategies of high concentrate feeding. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
3
39
0
3
Order By: Relevance
“…Concentrations of SCFA were analyzed using gas chromatography as described previously . Ammonia‐N concentration was measured photometrically using the indophenol method .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of SCFA were analyzed using gas chromatography as described previously . Ammonia‐N concentration was measured photometrically using the indophenol method .…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of SCFA were analyzed using gas chromatography as described previously. 17 Ammonia-N concentration was measured photometrically using the indophenol method. 18 Light absorbance of the prepared samples was measured at 655 nm wileyonlinelibrary.com/jsfa using a photometer (UV-1800, Shimadzu Corporation, Kyoto, Japan).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…The severity and duration of SARA conditions are particularly relevant for rumen health (Khafipour et al, 2009;Schwaiger et al, 2013). Recent research of our team observed that intermittent SARA conditions are stronger than persistent SARA conditions, likely because the rumen and its microbiota have less chance to adapt and the VFA are less absorbed across the reticulorumen wall Qumar et al, 2016;Wetzels et al, 2016). The latter is a major concern, as VFA absorption is essential for the regulation of the intraruminal pH and the alleviation of SARA conditions (Aschenbach et al, 2011;Schwaiger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Food goes down to the reticulorumen from the esophagus, and this is like a fermentation chamber which converts plant carbohydrate to volatile fatty acids, lactate, hydrogen, and methane which are used by the ruminant host. In ruminants, process starts with the peptic digestion in the abomasum [23].…”
Section: Physiology Of Dairy Animal's Digestive Systemmentioning
confidence: 99%